Comparative study on the corrosion behavior of TiCN-coated austenitic and ferritic stainless steels in geothermal environments - Agus Solehudin; Haipan Salam; Enda Permana; Atiek Rostika Noviyanti; Akrajas Ali Umaar; Risti Ragadhita (Teknomekanik, 2026)
Corrosion in stainless steel (SS) remains a critical limitation for its application, particularly in harsh environments such as geothermal systems. This study aims to evaluate the corrosion resistance of two SS substrates, namely SS 11-0 (ferritic) and SS 18-8 (austenitic), used as drill bit materials, both before and after the application of a TiCN protective coating. The coating was deposited by Physical Vapor Deposition (PVD) for 15, 25, and 35 minutes at 250°C. Corrosion resistance was assessed using a salt spray test with a 5% NaCl solution (pH 6–7) for 100 hours to simulate a neutral corrosive environment. Surface morphology and elemental composition were characterized using Field Emission Scanning Electron Microscopy–Energy Dispersive X-ray Spectroscopy (FESEM–EDS), while coating thickness and hardness were evaluated using Fischerscope® X-RAY XAN and Vickers microhardness testing, respectively. Corrosion performance was quantitatively analyzed using mass-loss-based corrosion rate calculations and polarization resistance measurements with a potentiostat instrument, providing insights into the electrochemical behavior of the coating–substrate system. The results demonstrate that increasing deposition time enhances coating thickness and overall coating quality. FESEM–EDS analysis confirms the successful formation of the TiCN layer and reveals changes in surface morphology and elemental composition after coating and corrosion exposure. Among the tested substrates, SS 18-8 consistently exhibits superior hardness, surface uniformity, and corrosion resistance compared to SS 11-0. Based on the weight loss method, the corrosion rates of uncoated and TiCN-coated SS 18-8 are 0.2600 mm/year and 0.1625 mm/year, respectively, both lower than those observed for SS 11-0. This enhanced performance is attributed to the synergistic effect between the TiCN coating and the Cr- and Ni-rich chemical composition of SS 18-8, which facilitates the formation of a stable and protective passive layer. These findings highlight the strong potential of TiCN-coated SS 18-8 for applications in geothermal environments under neutral corrosive conditions.